A Study on the Effect of Fresh Ginger on Cholesterol and Triglyceride Levels (Al-Farooq Journal of Sciences, 2026)
This study aims to investigate and clarify the changes that occur in the levels of total cholesterol, triglycerides, low-density lipoprotein (LDL), and high-density lipoprotein (HDL) in people who consume fresh ginger.     Blood samples were collected from a group of volunteers aged 23-55 years, and a complete lipid profile was measured on these samples, in addition to body weight measurement. The specific time period for consuming the ginger infusion was set at 30 days, in order to determine the extent of its effect and the subsequent changes in cholesterol and triglyceride levels.     Finally, in this study, it was noted in the results of these samples that consuming fresh ginger infusion for a sufficient period (30 days) led to a noticeable decrease in total cholesterol, triglycerides, and harmful lipids (LDL) levels. A decrease in body weight were also observed in study samples.